Vocational High School Teachers and Students’ Perception of the Emergency Curriculum During New Normal Era in Palembang - Neta Dian Lestari; Ramanata Disurya; Reva Maria Valianti; Rambat Nur Sasongko; Muhammad Kristiawan; Sudarwan Danim (AL-ISHLAH: Jurnal Pendidikan, 2022)
This research aims to investigate the implementation of full-day school during the new normal period carried out by four state vocational high schools in Palembang City during the new normal period after Covid-19. This study also aims to see the development and improvement of the quality of education with the emergency curriculum. The method used in this study is a descriptive case study, which describes the phenomenon or social phenomenon under study by describing the value of independent variables, both one or more variables (independent) based on indicators of the variables studied for exploration and classification. To collect the data, the researchers employed interviews with the participants. Meanwhile, content analysis was used to analyze the data. Based on the results of the research, namely the perceptions of teachers and students against full-day school during the new normal as well as the implementation of emergency curriculum at state vocational high schools in Palembang City, it can be concluded that the respondents’ statements are in accordance with the questionnaire that the researcher has given to students with a value of 210 questionnaire respondents with a number of questions, namely 35 questions, the conclusion is 84.05% in the very high category. This implies the positive perceptions of both teachers and students in Palembang.